Report and discussion on the IEEE ComSoc TCGN Gigabit Networking Workshop 1995. - Sterbenz, J.P.G.
Presents a summary of the second Gigabit Networking Workshop. The focus of the workshop is on end-to-end (level 4) and higher issues. Topics discussed include: ATM and B-ISDN, TCP/IP over ATM, ATM role in the future Internet-based Global Information Infrastructure, traffic monitoring and middleware
Keywords: ATM; B-ISDN.; IEEE ComSoc TCGN Gigabit Networking Workshop 1995.; Internet-based Global Information Infrastructure; TCP/IP.; End-to-end issues; Level 4 issues; Middleware; Traffic monitoring